THE STRENGTH OF THE FAMILY AS THE PILLAR OF SOCIETY - Mukhammadiyeva Oliya Narzullaevna (Western European Studies, 2025)
The article examines the sanctity of the family as the cornerstone of society, as well as the influence of social, economic, spiritual, and moral processes within the family on the upbringing of children. It is emphasized that marriage serves as the foundation of family stability and plays a crucial role in addressing demographic challenges
Keywords: Family; marriage; demography; society